iRGD-mediated MPN functionalization of MSNs for targeted delivery of MIF: a potential strategy for placenta accreta spectrum therapy - Zeng, Fanying; Chen, Peng; Tong, Longxia; He, Guolin (Frontiers in Bioengineering and Biotechnology, 2025)
Placenta accreta spectrum (PAS) is a severe pregnancy complication characterized by abnormal placental invasion, leading to life-threatening hemorrhage during delivery. Current management strategies face challenges between the systemic side effects of pharmacological interventions and the risks of invasive surgery. This study develops a targeted nanotherapeutic platform using iRGD peptide-functionalized mesoporous silica nanoparticles (MSNs) coated with metal–phenolic networks (MPNs) for mifepristone (MIF) delivery. The MPN-coated MSNs exhibited enhanced drug-loading capacity (275 μg/mg) and sustained-release profiles (83.3% release over 48 h). In vitro studies demonstrated excellent biocompatibility and selective uptake in trophoblast cells via αvβ3 integrin targeting. In a pregnant mouse model, the internalization RGD peptide (iRGD)-modified nanoparticles showed preferential placental accumulation and induced significant abortion through targeted trophoblast apoptosis, as evidenced by reduced chorionic gonadotropin levels and histological analysis. Although this proof-of-concept study demonstrates a promising targeted therapeutic strategy using healthy animal models, we acknowledge the limitation of not using true PAS pathological models. Our findings establish a foundation for developing precision nanomedicines for placental disorders, with future studies required to validate efficacy in disease-specific models.